2012
DOI: 10.1074/jbc.m111.280156
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Plays an Essential Role in Reducing Mitochondrial Production of Reactive Oxygen Species and Mutation of Mitochondrial DNA by Maintaining Mitochondrial Quantity and Quality in Yeast

Abstract: Background:The physiological importance of mitophagy in yeast has been largely unexplored. Results: Mitochondrial DNA deletion frequently occurs in mitophagy-deficient cells during nitrogen starvation because of overproduction of the reactive oxygen species from unregulated mitochondria. Conclusion: Mitophagy prevents excess reactive oxygen species production and mitochondrial DNA mutation. Significance: Our findings provide insight into mitophagy-related disorders such as Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
185
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(195 citation statements)
references
References 31 publications
5
185
1
3
Order By: Relevance
“…Besides apoptosis, HDAC5 depletion also induces an autophagic programme called mitophagy, a 'selfeating' process whereby ROS-producing mitochondria are eliminated. 23 This mechanism would help cells to survive as inhibition of HDAC5 silencing-dependent autophagy accelerates apoptosis, supporting the rationale for further testing autophagy inhibitors in conjunction with HDAC5 inhibition as a new combined therapy as already reported for broad-spectrum HDACi. 24,25 Modulation of VUDP-1/TBP2/thioredoxin expression, which consequently increases intracellular ROS, has been proposed as one of the mechanisms underlying HDACi-induced cell death.…”
Section: Discussionsupporting
confidence: 56%
“…Besides apoptosis, HDAC5 depletion also induces an autophagic programme called mitophagy, a 'selfeating' process whereby ROS-producing mitochondria are eliminated. 23 This mechanism would help cells to survive as inhibition of HDAC5 silencing-dependent autophagy accelerates apoptosis, supporting the rationale for further testing autophagy inhibitors in conjunction with HDAC5 inhibition as a new combined therapy as already reported for broad-spectrum HDACi. 24,25 Modulation of VUDP-1/TBP2/thioredoxin expression, which consequently increases intracellular ROS, has been proposed as one of the mechanisms underlying HDACi-induced cell death.…”
Section: Discussionsupporting
confidence: 56%
“…Defective removal of damaged mitochondria could lead to increased ROS amounts with consequent accumulation of mutations in mitochondrial and nuclear DNA, thus favouring cancer onset. Mitophagy has been implicated in the removal of damaged mitochondria containing high levels of ROS [136,137] and ROS accumulation can promote by itself mitophagy activation, for example through mitochondrial membrane depolarization and Parkin/PINK1 pathway activation [138,139], thereby inhibiting initial tumor growth. Indeed, Parkin deficient mice spontaneously develop hepatic tumors [140], and PINK1 mutations have been described in neuroblastoma [141].…”
Section: Mitochondrial Dynamics and Mitophagy In Cancermentioning
confidence: 99%
“…Subsequently, we tested whether the protective effect of MB against ACI injury was altered after mitophagy was inhibited. Given that ROS are recognized as central mediators of neuroinflammation and cytotoxicity caused by ischemia and that mitophagy blocks the generation of ROS (24,46), we examined the ROS levels after mitophagy was inhibited. We found that OGD caused an elevation of ROS and that MB suppressed this elevation of ROS.…”
Section: Mitophagy Mediates the Protection Of Mb Against Acute Ischemmentioning
confidence: 99%
“…In this process, damaged mitochondria are enveloped by double-membrane structures known as autophagosomes, which are then delivered to lysosomes for degradation (21)(22)(23). Thus, mitophagy plays a crucial role in controlling the quality of mitochondria by preventing the generation of ROS by dysfunctional mitochondria (24,25). Deficiency in mitophagy is associated with neurodegenerative diseases such as Parkinson's disease (26,27), Alzheimer's disease (28,29) and Huntington's disease (30).…”
Section: Introductionmentioning
confidence: 99%